RANCANG BANGUN PROTOTYPE MONITORING SYSTEM BERBASIS INTERNET OF THINGS PADA INKUBATOR PENETASAN TELUR AYAM - Devin Gede Herawan; I Kadek Agus Arta Yasa; Ida Bagus Alit Swamardika; Lie Jasa; I Wayan Arta Wijaya (Jurnal SPEKTRUM, 2025)
The hatching process of chicken eggs is highly dependent on a stable incubation environment, especially consistent and standard temperature and humidity. Fluctuations or instability of conditions within the incubator can significantly reduce the success rate of egg hatching (hatching) as well as degrade the quality of the chicks produced. In response to this challenge, this study developed an Internet of Things (IoT)-based monitoring system. The system is designed to monitor crucial parameters such as temperature, humidity, electric current, and voltage inside the incubator. The data collected from the monitoring is then transmitted using the ESP32 module to the ThingSpeak platform. This integration allows users to monitor the condition of the incubator at any time and remotely over an internet connection, providing flexibility and ease of supervision. The test results show that the developed system is able to provide accurate and responsive environmental condition data, and plays an important role in maintaining the stability of the incubation environment. This is expected to increase egg hatchability and support the production of better quality chicks.